Our tangled speech essays on language and culture - Mac Póilin, Aodán, 1948- (Ulster Historical Foundation, 2018)
This book provides a comprehensive overview of the Irish language revival north and south of Ireland, examining its successes and failures. It gives a fascinating account of historical attitudes towards the Gael and examines the complexities of linguistic and cultural identity.